Legal Protection of Children’s Rights in Conflict With The Law From Power Intervention - Hosnah, Asmak Ul; Jevis, Weldy; Nuraeny, Henny; Ahmad, Asmida (Universitas Muhammadiyah Purwokerto, 2025)
This study aims to examine the legal protection of the rights of children in conflict with the law, particularly in preventing power intervention within the juvenile criminal justice system in Indonesia. The background of this research is based on the prevalence of injustices faced by children due to weak oversight in the implementation of regulations, such as Law Number 11 of 2012 on the Juvenile Criminal Justice System and Law Number 35 of 2014 on Child Protection. The main issue raised is the gap between legal norms and their practical application in the field. The research methodology employs a normative and empirical juridical approach. Data were collected through document studies, in-depth interviews with law enforcement officers, children's families, and legal experts, as well as case study analyses, such as the case of Vina Dewi Arsita in Cirebon. The findings reveal instances of power abuse that harm children and highlight the weak implementation of restorative justice and rehabilitation principles within the juvenile criminal justice system. This study recommends a more effective legal protection model based on restorative justice, involving collaboration between law enforcement, government, families, and communities. It is hoped that this model will enhance transparency, justice, and the protection of children's rights.